A Detailed Paleoclimate Proxy Record for the Middle Danube Basin Over the Last 430 kyr: A Rock Magnetic and Colorimetric Study of the Zemun Loess-Paleosol Sequence - Laag, Christian; Hambach, Ulrich; Zeeden, Christian; Lagroix, France; Guyodo, Yohan; Veres, Daniel; Jovanović, Mladjen; Marković, Slobodan B. (Frontiers in Earth Science, 2021)
In mid-latitude Eurasia, loess-paleosol sequences (LPS) provide the most widespread sedimentary records of Quaternary paleoenvironmental evolution. In the Middle Danube Basin (MDB), these archives cover at least the last million years of climate history, and occasionally contain archeological findings. The studied Zemun LPS is located on the right bank of the Danube in Northern Serbia. The site was declared as a protected site, based on Paleolithic artifacts found on the riverbank and stemming from unknown stratigraphic levels of the loess cliffs exposed along the Danube. The present study aims to provide a stratigraphic, paleoenvironmental, and temporal context for the Zemun LPS by means of environmental magnetic and colorimetric methods. Our investigations result in a chronostratigraphic scheme allowing direct comparison with other well-established reference records in the MDB and elsewhere. Two potential tephra layers tentatively assigned to the so-called L2 and Bag tephras, which are both widespread in the MDB and beyond were investigated for their bulk magnetic properties. The resulting integrated age model suggests that the Zemun LPS records a detailed history of a quasi-continuous accumulation of mineral dust from Marine Oxygen Isotope Stage (MIS) 11–5a (c. 430–60 ka). The outcome of our integrative approach indicates a continuous aridification over the last four interglacial/glacial cycles and we discuss potential changes in seasonality over time.